The Role of Individual Knowledge in Functional Olive Oil Preferences: Does Self-Coherence Lead to Different Health Attributes Perception? - Giuseppe Di Vita; Alfio Strano; Giulia Maesano; Giovanni La Via; Mario D’Amico (Foods, 2020)
This study examined whether health cues influence the choices of olive oil consumers with different degrees of knowledge about the nutritional properties of olive oil. To this end, a direct survey on the consumption of healthy extra-virgin olive oil was implemented by examining the stated preferences of a sample of consumers. Two econometric analyses were carried out to identify the drivers of the consumption of olive oil with high polyphenol content. The logistic model was chosen as the most suitable method to answer the research questions. The results revealed a general consensus among consumers regarding the beneficial properties of olive oil consumption. Moreover, the findings show that different degrees of individual knowledge act as distinctive drivers in influencing the health perception of olive oil consumers. Finally, this study verified that, even for healthy foods, consumers’ choices are strongly dependent on their own self-coherence. As a consequence, consumers’ knowledge or beliefs that orientate their attitudes are influenced by different motivations and attributes.